Combined carbohydrate-protein supplementation improves competitive endurance exercise performance in the heat - Cathcart, A. J.; Murgatroyd, S. R.; McNab, A.; Whyte, L. J.; Easton, C. (European Journal of Applied Physiology, 2011)
Laboratory-based studies have demonstrated that adding protein (PRO) to a carbohydrate (CHO) supplement can improve thermoregulatory capacity, exercise performance and recovery. However, no study has investigated these effects in a competitive sporting context. This study assessed the effects of combined CHO-PRO supplementation on physiological responses and exercise performance during 8 days of strenuous competition in a hot environment. Twenty-eight cyclists participating in the TransAlp mountain bike race were randomly assigned to fitness-matched placebo (PLA 76 g/L CHO) or CHO-PRO (18 g/L PRO, 72 g/L CHO) groups. Participants were given enough supplements to allow ad libitum consumption. Physiological and anthropometric variables were recorded pre- and post-exercise. Body mass decreased significantly from race stage 1 to 8 in the PLA group (-0.75 ± 0.22 kg, P = 0.01) but did not change in the CHO-PRO group (0.42 ± 0.42 kg, P = 0.35). Creatine kinase concentration and muscle soreness were substantially elevated during the race, but were not different between groups (P = 0.82, P = 0.44, respectively). Urine osmolality was significantly higher in the CHO-PRO versus the PLA group (P = 0.04) and the rise in tympanic temperature from pre- to post-exercise was significantly less in CHO-PRO versus PLA (P = 0.01). The CHO-PRO group also completed the 8 stages significantly quicker than the PLA group (2,277 ± 127 vs. 2,592 ± 68 min, respectively, P = 0.02). CHO-PRO supplementation therefore appears to prevent body mass loss, enhance thermoregulatory capacity and improve competitive exercise performance despite no effect on muscle damage.